The rural household's entrepreneurship under the land certification in China - Fang Yang; Wei Liu; Ting Wen (Cogent Economics & Finance, 2022)
As China's economic growth slows down and the pressure of the economic downward increases gradually, the agricultural and rural economic development faces more serious challenges. Fortunately, thanks to the China's rural land certification, it guarantees the security and stability of property rights of land, and provides a huge development space for rural household's entrepreneurship, which promotes agricultural and rural economy greatly. In order to investigate the impact of the land certification on rural household's entrepreneurship in China, this paper uses China Rural Household Panel Survey data for the empirical analysis based on the panel Logit model. The results show that: (1) The land certification increases the probability of agricultural entrepreneurship by at least 25%, but it has no significant influences on non-agricultural entrepreneurship. (2) The rural land certification with boundary influences agricultural entrepreneurship more significant than that without boundary, and the land certification to household is more beneficial for agricultural rural household's entrepreneurship than that without to household. (3) The land certification mainly increases probability of agricultural entrepreneurship through the land transfer, labor allocation, and capital allocation. Moreover, the research of this study highlights the importance of standardizing rural labor market and accelerating land financial reform in creating conditions for agricultural entrepreneurship, which can provide effective data support for future rural policy-making.
Keywords: 330; Agricultural economics; land certification; agricultural entrepreneurship; nonagricultural entrepreneurship